2021
DOI: 10.3390/biomedicines9010039
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Monoclonal Antibody Therapy for Colorectal Cancers

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer deaths worldwide. Recent advances in recombinant DNA technology have led to the development of numerous therapeutic antibodies as major sources of blockbuster drugs for CRC therapy. Simultaneously, increasing numbers of therapeutic targets in CRC have been identified. In this review, we first highlight the physiological and pathophysiological roles and signaling mechanisms of currently known and emerging therapeutic targets, including growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 178 publications
(186 reference statements)
0
14
0
Order By: Relevance
“…Many of these inhibitors are being investigated in phase II clinical studies in CRC, while the US FDA has approved several drugs for targeted therapy in clinical application, as listed in Table 2 . These small molecule inhibitors and monoclonal antibodies can be used as monotherapy or combined with conventional therapies to increase the therapeutic efficacy and cancer specificity ( To et al, 2020 ; Hwang et al, 2021 ). For instance, cetuximab and panitumumab are monoclonal antibodies that target EGFR and can be used as monotherapy or combined with chemotherapy to treat patients with RAS wild-type metastatic CRC ( Hayashi et al, 2017 ; Garcia-Foncillas et al, 2019 ).…”
Section: Targeting Colorectal Cancer Metabolismmentioning
confidence: 99%
“…Many of these inhibitors are being investigated in phase II clinical studies in CRC, while the US FDA has approved several drugs for targeted therapy in clinical application, as listed in Table 2 . These small molecule inhibitors and monoclonal antibodies can be used as monotherapy or combined with conventional therapies to increase the therapeutic efficacy and cancer specificity ( To et al, 2020 ; Hwang et al, 2021 ). For instance, cetuximab and panitumumab are monoclonal antibodies that target EGFR and can be used as monotherapy or combined with chemotherapy to treat patients with RAS wild-type metastatic CRC ( Hayashi et al, 2017 ; Garcia-Foncillas et al, 2019 ).…”
Section: Targeting Colorectal Cancer Metabolismmentioning
confidence: 99%
“…e therapeutic effect was mainly mediated by potent ADCP induced by Kupffer cells (macrophages residing in the liver) and monocytes [30][31][32]. Although the potential of perioperative antibody treatment to prevent metastasis development has not been investigated extensively in the clinic [33], one study showed increased 7year survival and reduced overall mortality in patients with primary colorectal cancer, who were treated postoperatively with anti-EpCAM antibodies [34]. Treatment had no effect on the local recurrence of the primary tumor but reduced the occurrence of distant metastases in approximately 30% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the KRAS gene occur early in the development of many cancers and often lead to the up-regulation of RAS proteins and their downstream effector pathways [8]. Having in mind that over expression of EGFR has been found in 80% of CRC and has been as-sociated with the progression of the malignant process and poor prognosis, it is no surprise that targeted therapy based on the application of monoclonal antibodies, such as cetuximab and panitumumab that inhibit EGFR signalling, has been shown to be very effective [9,10]. Namely, the action of these monoclonal antibodies is directed to the extracellular domain of EGFR where they block binding of a ligand, which results in a subsequent inhibition of the downstream RAS-RAF-MEK-ERK signalling pathway.…”
Section: Introductionmentioning
confidence: 99%